TANGGUNGJAWAB NEGARA TERHADAP WARGA NEGARA INDONESIA YANG MENJADI KORBAN PEMBAJAKAN KAPAL DITINJAU DARI HUKUM LAUT INTERNASIONAL - Laila Fitriani Siregar; Suhaidi Suhaidi; Arif Arif (Journal of USU International Law, 2017)
THE RESPONSIBILITY OF THE STATE TOWARDS THE CITIZEN OF INDONESIA WHO BECAME VICTIMS OF THE HIJACKING OF THE SHIP IN TERMS OF INTERNATIONAL LAW OF THE SEA ( A case study of piracy Ship Mv Delay Brahma And Tongkang Anand 12 by a group of Abu Sayyaf -2016). ABSTRACT Laila Fitriani Siregar * Prof.Dr.Suhaidi.SH.,M.H. ** Arif SH., M.H *** Ship hijacking is one of kind of transnational crime that disrupts international shipping lines and sea order. The arrangement of ship hijacking has been regulated in various international agreements which are among others : United Nation Convention on the Law of the Sea ( UNCLOS 1982), Convention for the Supression of Unlawful Acts Againts the Safety of Maritime Navigation ( The SUA Convention), and some of PBB resolutions about piracy. In 2016, 10 Indonesian citizens become victims of ship hijacking carried out by abu sayyaf group when they crossing at the fhilipin watres. The problem in this writing is : What is the arrangement of ship hijacking at the sea under international maritime law and national law, How is law enforcement of ship hijacking in the territorial sea of fhilipina according to the perspective of international law, and how is the responsibility of the rebublic of indonesian to its citizens who are victims of the hijacking of ships by abu sayyaf group. This writing is made through normative legal research using primary, secondary, and tertiary data. Combined data through literature study and analized normatively-qualitative. State responsibility to its citizens who are victims of hijacking of ships abroard can be done through with diplomatic rights owned by the state. The provisions of international law regulated in UNCLOS and other international treaties require each country to arrest and prosecute any person or ship suspected of being a perpetrator of piracy through state-owned jurisdiction either in its territory or at the high seas. The establishment of a special court of piracy is necessary to provide legal certainty that affirms law enforcement of ship hijacking at sea and handling of pirate ship perpetratos at the sea. Keywords : Diplomatical Protection, Victims of Piracy, The Responsibility State